THE IMPACT OF ARTIFICIAL INTELLIGENCE ON THE GLOBAL ECONOMY AND PRODUCTIVITY - Petrova, Plamena (E-Journal VFU, 2025)
This research aims to examine the economic effects of the widespread integration of artificial intelligence in various sectors of the economy. Data from national and international sources is presented, tracking trends in AI adoption, economic growth rates, productivity, income distribution over time, and social inequality.